Barriers and facilitators to physical activity among ethnic Chinese children: a qualitative systematic review. Issue 12 (22nd December 2020) - Wang, Haiquan; Swain, Subhashisa; Luo, Jihao; Blake, Holly; Chattopadhyay, Kaushik
ABSTRACT: Objective: The review aimed to synthesize the barriers and facilitators from the available studies that explored physical activity among ethnic Chinese children and uncover any differences or similarities in these barriers and facilitators. Introduction: Physical activity promotes overall health, fitness, and well-being in children, yet prevalence of this has been low among ethnic Chinese children who reside in either Chinese and non-Chinese territories. Research has been conducted to explore the barriers and facilitators to physical activity among ethnic Chinese children. However, no qualitative systematic review has been conducted to synthesize these barriers and facilitators. Inclusion criteria: Studies were considered for inclusion if they explored the barriers and facilitators to physical activity among ethnic Chinese children aged six to 17 years in either Chinese or non-Chinese territories, or among people who had responsibility for them in school, home, and community settings. The review included studies that focused on their views, experiences, attitudes, understandings, perceptions, and perspectives. Studies were included if they focused on qualitative data including, but not limited to, designs such as phenomenology, ethnography, grounded theory and action research. In addition, the authors considered cross-sectional surveys to find any free text relating to the review question. Methods: MEDLINE, Embase, CINAHL, PsycINFO, BNI, AMED, Web of Science, Scopus, CNKI, Wanfang and VIP databases were searched to identify published studies. The search for unpublished studies included EThOS, OpenGrey, ProQuest Dissertations and Theses, CNKI and Wanfang. Databases were searched from their inception dates to 10 December 2018 and no language restrictions were applied. The JBI guidelines for qualitative systematic reviews were followed in conducting the review. The JBI process of meta-aggregation was used to identify categories and synthesize findings. Results: Out of 9460 records identified, 11 qualitative studies met the eligibility criteria and were included in the review. Using the JBI checklist for qualitative research (10 criteria), the critical appraisal scores of the majority of studies ranged from a moderate score of 6 (n = 1) to a high score of 7 and above (n = 9). Seven studies were from China, two from Australia, one each from the United Kingdom and the United States. The sample size ranged from 12 to 115 participants. A total of 56 findings were extracted and aggregated into 21 categories, based on the similarity of meaning. From studies conducted in the Chinese territories, four synthesized findings (personal, socio-cultural, environmental, and policy- and program-related barriers and facilitators) were aggregated from 37 extracted findings and 14 aggregated categories. From studies conducted in the non-Chinese territories, only two synthesized findings (personal and socio-cultural barriers and facilitators) were derived from 19 extracted findings and seven aggregated categories. Based on the ConQual scores, confidence in the synthesized findings was moderate. Conclusions: Four broad themes emerged from the participants' accounts, namely personal, socio-cultural, environmental, and policy- and program-related factors. Barriers and facilitators at the personal and socio-cultural level (e.g., parents and teachers) were most frequently cited, reflecting the importance of children's self-influence and the role of adults. Future interventions are needed to address the identified barriers and enhance the facilitators. Systematic review registration number: PROSPERO CRD42018097124